Liar Liar: Experimental Evidence of the Effect of Confirmation‐Reports on Dishonesty. (2nd November 2017) - Duncan, Denvil; Li, Danyang
Abstract : We identify the effect of confirmation‐reports on dishonesty using data from an experiment where subjects are asked to roll a die and report its outcome using either a self‐report or confirmation‐report mechanism. We find that relative to self‐reports, confirmation‐reports have a positive effect on the share of subjects who report honestly. The effect on the magnitude of lies told depends greatly on the accuracy of the prefilled information on the confirmation‐report. We argue that these results are driven by changes in the intrinsic costs of lying induced by the confirmation report.